2021
DOI: 10.1007/s00126-021-01080-1
|View full text |Cite
|
Sign up to set email alerts
|

Mineral-scale variation in the trace metal and sulfur isotope composition of pyrite: implications for metal and sulfur sources in mafic VMS deposits

Abstract: The link between metal enrichment and the addition of a magmatic volatile phase in volcanogenic massive sulfide deposits and actively forming seafloor massive sulfide deposits remains poorly characterized. This is especially true when considering how metal, sulfur and fluid flux change with time. In this study, we combine in situ sulfur isotope (δ 34 S; n = 31) measurements with trace metal chemistry of pyrite (n = 143) from the Mala VMS deposit, Troodos, Cyprus. The aim of our study is to assess the links bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 117 publications
(242 reference statements)
0
10
0
Order By: Relevance
“…Notably, several δ 34 S values at Semenov‐1 plot at <0‰, and, coupled with an enrichment of Au and Ag in the nearby Semonov‐2 vent field, are interpreted as evidence of magmatic volatile influx (Melekestseva et al., 2014, 2017). Our data from the exposed fault surface at Semenov‐4 does not support the presence of a magmatic volatile phase, indicating that if a magmatic volatile phase was present in the Semenov vent field cluster, it was a localized phenomenon, both temporally and spatially (Herzig et al., 1998; Martin et al., 2021). The average δ 34 S value for all analyses in this study is consistent with the contribution of sulfur from TSR and the leaching of host rocks at 6.4 ± 1.3‰ ( n = 45, 1 σ ).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Notably, several δ 34 S values at Semenov‐1 plot at <0‰, and, coupled with an enrichment of Au and Ag in the nearby Semonov‐2 vent field, are interpreted as evidence of magmatic volatile influx (Melekestseva et al., 2014, 2017). Our data from the exposed fault surface at Semenov‐4 does not support the presence of a magmatic volatile phase, indicating that if a magmatic volatile phase was present in the Semenov vent field cluster, it was a localized phenomenon, both temporally and spatially (Herzig et al., 1998; Martin et al., 2021). The average δ 34 S value for all analyses in this study is consistent with the contribution of sulfur from TSR and the leaching of host rocks at 6.4 ± 1.3‰ ( n = 45, 1 σ ).…”
Section: Discussionmentioning
confidence: 72%
“…When considering primary concentric zonations, Se is enriched between the zones of Co and Ni enrichment . This indicates a decoupled relationship between Se and Ni-Co. Selenium-rich zones could have formed from several processes: magmatic degassing episodes, as Se has an affinity for the volatile phase (Martin et al, 2021), variations in fluid redox, with oxidized fluids being able to transport higher amounts of Se (Huston et al, 1995a(Huston et al, , 1995b, or pulses of higher temperature fluid, as Se is preferentially enriched in high-temperature pyrite generations (Butler & Nesbitt, 1999).…”
Section: Metal Zonations In Pyritementioning
confidence: 99%
“…Numerous primary textures preserved in the ABM deposit have features that are similar to modern seafloor massive sulfide (SMS) deposits (Ames et al 1993 ; Grant et al 2018 ) and those found in well-preserved and relatively undeformed ancient VMS deposits (Eldridge et al 1983 ; Martin et al 2021 ). In assemblage 1, banding and finer-grained laminations interpreted to be primary occur as millimeter to centimeter layers defined by varying sulfide mineralogy and grain size (Fig.…”
Section: Observations and Resultsmentioning
confidence: 92%
“…For example, pyrite from assemblage 2 has elevated Se, Co, and Ni compared to the assemblage 1 (Figs. 11 c and 12 c), indicative of formation at higher temperatures (Huston et al 1995 ; Genna and Gaboury 2015 ; Martin et al 2021 ). Elevated Se content in pyrite (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Data reduction was performed using GLITTER TM software [34], which allows for baseline subtraction, the integration of the signal over a selected time resolve area and quantification using known concentrations of the external and internal standards. The isotope 57 Fe was used as the internal standard, assuming a stoichiometric composition.…”
Section: Methodsmentioning
confidence: 99%